Implementation of the Chinese Government Scholarship (CGS) Program in Changing China's Nation Branding in Indonesia - Wiraloka, Puspita; Budiman, Imam; Ismail, Ilham Ahmad; Azeila, Azzara; Marzuki, Salsabila Putri (Journal of Governance and Social Policy, 2025)
Chinese Government Scholarship (CGS) is a scholarship program offered by the Chinese government as one of the instruments used to enhance China's nation branding in Indonesia. This research aims to analyze the implementation of the Chinese Government Scholarship (CGS) program and its contribution to improving China's nation branding in Indonesia. In preparing this thesis, the researcher utilized observation data collection techniques and document analysis. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. The results of this study indicate that the Chinese Government Scholarship program has successfully become a strategic instrument for nation branding employed by China to enhance its positive image in Indonesia.